Pour une histoire culturelle de la musique. - Igor Contreras Zubillaga; Elsa Rieu (Transposition)
This interview with Karen Painter has provided us with the opportunity of inquiring about her personal trajectory, her views on musicology, and certain key aspects of her work. From this dialogue, there emerges a musicologist concerned about relocating the study of music within the discipline of history, and engaging her object of study in the wider epistemological and historiographic debates.